Eradication of Staphylococcus aureus Biofilm Infections Using Synthetic Antimicrobial Peptides. (7th February 2017) - Zapotoczna, Marta; Forde, Éanna; Hogan, Siobhan; Humphreys, Hilary; O'Gara, James P; Fitzgerald-Hughes, Deirdre; Devocelle, Marc; O'Neill, Eoghan
Abstract: Here, we demonstrate that antimicrobial peptides (AMPs) are an effective antibiofilm treatment when applied as catheter lock solutions (CLSs) against S. aureus biofilm infections. The activity of synthetic AMPs (Bac8c, HB43, P18, Omiganan, WMR, Ranalexin, and Polyphemusin) was measured against early and mature biofilms produced by methicillin-resistant S. aureus and methicillin-susceptible S. aureus isolates from patients with device-related infections grown under in vivo–relevant biofilm conditions. The cytotoxic and hemolytic activities of the AMPs against human cells and their immunomodulatory potential in human blood were also characterized. The D-Bac8c 2, 5Leu variant emerged as the most effective AMP during in vitro studies and was also highly effective in eradicating S. aureus biofilm infection when used in a CLS rat central venous catheter infection model. These data support the potential use of D-Bac8c 2, 5Leu, alone or in combination with other AMPs, in the treatment of S. aureus intravenous catheter infections.